New oil‐in‐salt liquid‐phase microextraction on permutite for the extraction and concentration of alkaloids in Coptis chinensis. Issue 6 (9th February 2017) - Gao, Ping; Chen, Xuan; Hu, Shuang; Bai, Xiaohong; Luo, Miaomiao
Abstract : A novel oil‐in‐salt liquid‐phase microextraction was developed and introduced for the extraction and concentration of the trace levels of active alkaloids in Coptis chinensis prior to being analyzed by high‐performance liquid chromatography with ultraviolet detection. Also, the oil‐in‐salt extraction mechanism was analyzed, the enrichment factor and extraction recovery were redefined, and the proposed method was compared with other methods. In the approach, the mixed solvent of pentanol/octanol (6:4, v/v) and NaCl (20% w/v) are immobilized on the permutite surface in turn to form oil‐in‐salt double membranes, through which the target analytes can be molecularized though salting‐out effect and be extracted by organic solvent. The main parameters affecting the approach were investigated and optimized. Under the optimized conditions, the enrichment factors of the analytes were 30–117, the linear ranges were 0.002–2 μg/mL for jatrorrhizine, coptisine, and palmatine, and 0.001–3 μg/mL for berberine ( r 2 ≥ 0.9923). The limits of detection were less than 1 ng/mL. Satisfactory recoveries (84.3%–120.3%) and precision (0.9%–7.5%) were also obtained. These results confirm that the approach is a simple and reliable sample pretreatment procedure and allows for the quantification of active alkaloids in C. chinensis at actual concentration levels.